Treatment strategies and antibiotic usage practices in mastitis management in Kenyan smallholder dairy farms - Muloi, Dishon; Ibayi, Eugine; Nyotera, Sharon; Kirimi, Hildah; Abdi, Abdullahi; Mutungwa, Silvester; Chemutai, Abigael; Moodley, Arshnee (2024)
Mastitis is a common driver of antibiotic use in dairy farms and is exacerbated in low-income settings by the lack of diagnostics and treatment strategies. This study assessed the decision-making process of animal health providers (AHPs) in managing mastitis in small-holder dairy farms in Kiambu County, Kenya. Data were collected from 114 AHPs on: (i) demographics (age, sex, education level, years of veterinary practice), (ii) decision-making process relating to management of clinical mastitis, (iii) antibiotic use practices (brands, frequency), and (iv) attitudes and perceptions towards udder health and mastitis management.